G9a and Sirtuin6 epigenetically modulate host cholesterol accumulation to facilitate mycobacterial survival. - Praveen Prakhar; Bharat Bhatt; Gaurav Kumar Lohia; Awantika Shah; Tanushree Mukherjee; Ullas Kolthur-Seetharam; Nagalingam R Sundaresan; Raju S Rajmani; Kithiganahalli Narayanaswamy Balaji (PLoS Pathogens, 2023)
Cholesterol derived from the host milieu forms a critical factor for mycobacterial pathogenesis. However, the molecular circuitry co-opted by Mycobacterium tuberculosis (Mtb) to accumulate cholesterol in host cells remains obscure. Here, we report that the coordinated action of WNT-responsive histone modifiers G9a (H3K9 methyltransferase) and SIRT6 (H3K9 deacetylase) orchestrate cholesterol build-up in in vitro and in vivo mouse models of Mtb infection. Mechanistically, G9a, along with SREBP2, drives the expression of cholesterol biosynthesis and uptake genes; while SIRT6 along with G9a represses the genes involved in cholesterol efflux. The accumulated cholesterol in Mtb infected macrophages promotes the expression of antioxidant genes leading to reduced oxidative stress, thereby supporting Mtb survival. In corroboration, loss-of-function of G9a in vitro and pharmacological inhibition in vivo; or utilization of BMDMs derived from Sirt6-/- mice or in vivo infection in haplo-insufficient Sirt6-/+ mice; hampered host cholesterol accumulation and restricted Mtb burden. These findings shed light on the novel roles of G9a and SIRT6 during Mtb infection and highlight the previously unknown contribution of host cholesterol in potentiating anti-oxidative responses for aiding Mtb survival.